Hide and seek – Infection rates and alkaloid concentrations of Epichloë festucae var. lolii in Lolium perenne along a land‐use gradient in Germany. (6th October 2017) - König, J.; Fuchs, B.; Krischke, M.; Mueller, M. J.; Krauss, J.
Abstract: The common forage grass Lolium perenne has evolved with the systemic fungal endophyte Epichloë festucae var. lolii . The endophyte provides herbivore resistance to the grass due to defensive alkaloids, some of which are toxic to grazing livestock. In this field study, we determine whether distribution of the endophyte‐grass association changes along a land‐use intensity gradient on 87 managed grasslands in three German regions. Endophyte infections were detected in 66% of the studied sites and infection rates within infected sites ranged from 1% to 95%. Alkaloid concentrations of lolitrem B (vertebrate toxin) exceeded the toxicity thresholds in 50 (14%) of 351 infected plants and of peramine (invertebrate deterrent/toxin) in 12 (3%) of 351 plants. Infection rates and alkaloid concentrations were not significantly affected by land‐use intensity and region, but alkaloid concentrations were higher in summer compared to spring. We conclude that risks for livestock intoxication are currently low, as (i) average alkaloid concentrations per grassland were always below toxicity thresholds and as (ii) none of the grasslands was dominated by L. perenne . We suggest avoidance of grass monocultures in Europe to keep intoxication risks for livestock low; we also recommend regular examination of seeds and grasslands, as seed producers might accidentally distribute infected seeds, and as climate warming might further enhance the distribution of Epichloë endophytes in European grasslands.